Design an automobile simulation test rig - Perabu, Moorty (2013)
This project report deals with dynamic behaviour of Car body with simulation of Sinusoidal wave and Random excitation wave and also modal analysis using theoretical and experimental analysis method, to study selection of test rig development. This project report is to study the design of an automobile simulation test rig using working model 2D analysis and also modal analysis, finally compare it. The structural three-dimensional solid modelling of car body was developed using the SOLIDWORK drawing software. The modal analysis was then performed using ANSYS 14.0 (Modal Analysis). Finally, the experimental modal analysis was performed using Impact Hammer Testing method. The natural frequency of the mode shape is determined and comparative study was done from both method results. The comparison between natural frequencies of modal analysis ANSYS modelling and model testing shows the closeness of the results. From the results, the percentage error had been determined and the limitation in the natural frequency of the car body is observed. The results of this project shown the mode shapes of car body simulation are generally is not in agreement with the experimental value and the frequencies of the experimental modal analysis are a bit different with the frequencies of the simulation. The percentage error is bit high because there are some errors occur during the experimental modal analysis. The experimental modal analysis is conducted with fix condition which effect test rig by using spring as a base of the plate is a factors as the higher percentage error. The comparison between two concept design also been done using working model 2D by sinusoidal wave and random wave excitation. As result, the best studies deformation were been conducted through concept solenoid Actuator Test rig, therefore that concept has been chosen according to the concept scoring method.